FLATCON® CPV module with 36.7% efficiency equipped with four‐junction solar cells. (19th November 2014) - Steiner, Marc; Bösch, Armin; Dilger, Alexander; Dimroth, Frank; Dörsam, Tobias; Muller, Matt; Hornung, Thorsten; Siefer, Gerald; Wiesenfarth, Maike; Bett, Andreas W.
Abstract: In this paper we present the application of high efficiency four‐junction solar cells using SOITEC bonding technology under a Fresnel lens optic and in a FLATCON®‐type CPV module. We demonstrate very high performance. The measurement of a sub‐module, consisting of a four‐junction solar cell adjusted under a single Fresnel lens, showed an efficiency of 38.9%. An 829.6 cm 2 sized FLATCON®‐type CPV module yielded in an efficiency of 35.0% and 36.7% at CSOC and CSTC, respectively. Thus, both, the sub‐module and the CPV module showed record values, which prove the usefulness of high efficiency four‐junction solar cells in CPV applications. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : In this paper, we present the CPV application of high‐efficiency four‐junction solar cells using SOITEC bonding technology. The measurement of a sub‐module, consisting of a four‐junction solar cell and a single Fresnel lens, showed an efficiency of 38.9%. An 830‐cm 2 sized FLATCON‐type CPV module yielded in an efficiency of 35.0% and 36.7% at CSOC and CSTC, respectively. Thus, both sub‐module and module showed record values, which prove the usefulness of four‐junction solar cells in CPV applications.